Biodiversity and Ichthyofaunal Richness of Fish Population in River Subansiri in the Downstream of the Lower Subansiri Hydro-electric Power Project Dam, Assam, India - , Imran Hussain, Ayub Ali, Imtiaz Ahmed, Rinku Gogoi, Jiten Sarma, Rajdeep Dutta, Sheetala Chintey (Archives of Current Research International, 2024)
The present study on fish diversity, assemblages, water quality and conservation status of Subansiri river, Assam was conducted for a period of one year in the mainstream. Altogether 55 fish species belonging to 42 genera, 24 families and 10 orders were recorded from the river. The largest group Cypriniformes contributed 3 families (12.50%), 15 genera (35.71%) and 20 species (36.36%). As per IUCN conservation status, 51 (92.72%) species were recorded as Least Concern, 2 (3.64%) species under near threatened, 1 (1.82%) species under vulnerable and 1 (1.82%) species under endangered category. The mean value with regard to Physico-chemical parameters of river Subansiri was moderate. The Bray-Curtis similarity prepared for river Subansiri showed the highest similarity between stations 2 and 3 in the pre-monsoon season. The CCA analysis indicates that alkalinity, TDS, temperature, conductivity, pH, dissolved oxygen, transparency and velocity are the most important parameters influencing the fish distribution and assemblage in the river.